Behavior management-based applied behaviour analysis within dental examination of children with autism spectrum disorder - Taufiqi Hidayatullah; Hendriati Agustiani; Arlette Suzy Setiawan (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Autism spectrum disorder (ASD) is a developmental disorder with three main characteristics: communication disorders, social interaction disorders and repetitive behavior. The main problem faced when treating child patients with this disorder is the difficulty of establishing communication with the result that they are unable to understand instructions. One form of therapy frequently applied in cases of autism is that of applied behavior analysis (ABA). It is easier for children with ASD to absorb information visually. Purpose: The purpose of this study was  to evaluate the effectiveness of ABA-based behavior management using visual media in the form of picture cards for oral examination of children with ASD. Methods: The study design was observational descriptive in nature and the sample selection was based on purposive sampling. The study was conducted by observing changes in childrens’ behavior during treatment administered four times a month. The subjects were 13 children with ASD who met the study criteria and were receiving treatment for autism at Prananda special school in Bandung. The collated data related to changes in subjects’ behavior observed during four meetings assessed on the basis of score 1 confirming compliance with instructions and 0 indicating non-compliance. A Kruskal-Wallis statistical analisysis test was used to analyze the data. Results: The results showed a general increase in the former over the latter initial behavior during treatment. Statistical analysis showed that the coefficient of Kruskal-Wallis was meaningful in terms of statistical significance with a p-value of 26.947 (<0.05). The multiple comparison value for average ranks was 15.68 (SD 18.69). Conclusion: The conclusion of this study is that the application of a behavior management-based analytical methodology is effective in supporting the oral examination of children with ASD.